Satiety: a gut–brain–relationship - Ghinwa M. Barakat; Wiam Ramadan; Ghaith Assi; Noura B. El Khoury (Journal of Physiological Sciences)
Abstract Many hormones act on the hypothalamus to control hunger and satiety through various pathways closely associated with several factors. When food is present in the gastro intestinal (GI) tract, enteroendocrine cells (EECs) emit satiety signals such as cholecystokinin (CCK), glucagon like peptide-1 (GLP-1) and peptide YY (PYY), which can then communicate with the vagus nerve to control food intake. More specifically, satiety has been shown to be particularly affected by the GLP-1 hormone and its receptor agonists that have lately been acknowledged as a promising way to reduce weight. In addition, there is increasing evidence that normal flora is also involved in the peripheral, central, and reward system that impact satiety. Moreover, neurologic pathways control satiety through neurotransmitters. In this review, we discuss the different roles of each of the GLP-1 hormone and its agonist, gut microbiomes, as well as neurotransmitters and their interconnected relation in the regulation of body’s satiety homeostasis.